2003
DOI: 10.1161/01.cir.0000089084.48655.49
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Culture-Modified Mononuclear Cells Confer Vascular Protection After Arterial Injury

Abstract: Background-Bone marrow-derived cells have been shown to contribute to endothelial replacement after vascular injury.In vitro culture of peripheral blood mononuclear cells produces cells with phenotypic characteristics of endothelium. To test the hypothesis that delivery of autologous culture-modified mononuclear cells (CMMCs) to injured arteries could attenuate the vascular response to injury, a rabbit model was studied. Methods and Results-Rabbit peripheral blood mononuclear cells were cultured in endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
3
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(136 citation statements)
references
References 31 publications
8
122
3
3
Order By: Relevance
“…Interestingly, the repair of vascular injury with EPCs is associated with normalization of endothelial function at the site of the injury. 5 Conversely, the repair of vascular injury may be impaired in the setting of endothelial dysfunction, which may be attributed to 2 possible mechanisms. A recent study demonstrated that the degree of endothelial dysfunction correlated with the number of EPCs.…”
Section: Localization and Distribution Of The Endotheliummentioning
confidence: 99%
“…Interestingly, the repair of vascular injury with EPCs is associated with normalization of endothelial function at the site of the injury. 5 Conversely, the repair of vascular injury may be impaired in the setting of endothelial dysfunction, which may be attributed to 2 possible mechanisms. A recent study demonstrated that the degree of endothelial dysfunction correlated with the number of EPCs.…”
Section: Localization and Distribution Of The Endotheliummentioning
confidence: 99%
“…However, the origin of the double-positive EPCs is still under debate. It could be demonstrated by Gulati et al that the vast majority of EPCs arose from a CD14 pos subpopulation of peripheral blood cells, whereas late outgrowth endothelial cells develop exclusively from the CD14 neg fraction (32). Nevertheless, with respect to the characteristics and functional properties Urbich et al reported that adherent cells derived from CD14 pos or CD14 neg MNCs show equal expression of endothelial marker proteins and capacity for clonal expansion (17).…”
Section: Cell Culturementioning
confidence: 99%
“…[13][14][15][16][17][22][23][24]81,[97][98][99][100] Autologous EPC transplantation may be used to promote rapid re-endothelialization and restoration of homeostasis in blood vessels injured during revascularization procedures 22-24,97-100 or for seeding of prosthetic grafts, stents, or engineered blood vessels to create a bioactive endothelial layer. 22,23,97,98 We showed recently that transplantation of autologous PB-EPCs leads to rapid re-endothelialization of balloon-denuded rabbit carotid arteries, resulting in significant reduction of neointimal hyperplasia. 23 Using a similar approach, Gulati et al 98 reported that transplantation of cultured autologous MNCs at the time of injury markedly reduced neointima hyperplasia in association with rapid re-endothelization of the damaged vessel.…”
Section: Endothelial Cell Therapy For Vascular Repair and Bioengineermentioning
confidence: 99%
“…22,23,97,98 We showed recently that transplantation of autologous PB-EPCs leads to rapid re-endothelialization of balloon-denuded rabbit carotid arteries, resulting in significant reduction of neointimal hyperplasia. 23 Using a similar approach, Gulati et al 98 reported that transplantation of cultured autologous MNCs at the time of injury markedly reduced neointima hyperplasia in association with rapid re-endothelization of the damaged vessel. Oth- ers have shown the ability of transplanted EPCs to restore endothelial function in damaged vessels.…”
Section: Endothelial Cell Therapy For Vascular Repair and Bioengineermentioning
confidence: 99%